„Silę ucho”, czyli co słychać w przekładzie. Niemieckojęzyczne warianty wiersza Skakanka ufoistki Mirona Białoszewskiego na tle zabiegów „przekładania” codzienności na język poetycki - Burba, Aleksandra (Wydawnictwo Poznańskie Studia Polonistyczne i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The article has been derived from a chapter of an MA thesis on everyday speech in Miron Białoszewski’s work. The text focuses on exposition of methodological assumptions - the notion of everyday speech and its translation into poetic language in Białoszewski’s works. In particular, the article discusses a series of non-professional translations of the poem UFO agent’s skipping rope into German, as an example of the functioning of the dominant of everyday speech in translations of Białoszewski’s poetry.
“I strain my ear”, or what can be heard in translation. German variants of the poem Ufo Agent’s Skipping Rope by Miron Białoszewski, with reference to his technique of “translating” everyday life into poetic language
Keywords: everyday life in poetic language; everyday speech; Miron Białoszewski’s poetry; non-professional translation into German